2015
DOI: 10.1109/jphot.2015.2426874
|View full text |Cite
|
Sign up to set email alerts
|

Joint Time and Frequency Dissemination Network Over Delay-Stabilized Fiber Optic Links

Abstract: A precise fiber-based time and frequency dissemination scheme for multiple users with a tree-like branching topology is proposed. Through this scheme, ultra-stable signals can be easily accessed online anywhere along the fiber without affecting other sites. The scheme is tested through an experiment, in which a modulated frequency signal and a synchronized time signal are transferred to multiple remote sites over a delay-stabilized fiber optic links that are over 50 km long. Results show that the relative stab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In particular, it enables fiber-referenced VLBI without the need for multiple hydrogen masers. Our technique does not entail absolute timing [66], in contrast to other recent fiber-based time-and-frequency transfer schemes [2][3][4][5][6][9][10][11][12][13][14][15][16][17]28,30,31,36,[42][43][44][45][46]50,55,64,70].…”
Section: E General Discussionmentioning
confidence: 99%
“…In particular, it enables fiber-referenced VLBI without the need for multiple hydrogen masers. Our technique does not entail absolute timing [66], in contrast to other recent fiber-based time-and-frequency transfer schemes [2][3][4][5][6][9][10][11][12][13][14][15][16][17]28,30,31,36,[42][43][44][45][46]50,55,64,70].…”
Section: E General Discussionmentioning
confidence: 99%
“…Note that the wavelength of LD3 (internally modulated DFB laser) used to modulate FR is λ3 = 1547.72 nm, and the wavelength of LD4 (electro-absorption modulated DFB laser) used to modulate TR is λ4 = 1549.32 nm, while the PD3 and PD4 are as same as PD1 and PD2, respectively. Different wavelengths are used to avoid the influences of back-scattering and reflection [10], [21]. Next, a phase frequency detector (PFD, HMC439) is used to measure the round-trip phase difference (φrt) between FL and return-back 1 GHz signal (Frt), and a time interval counter (TIC, SR620) is used to measure the round-trip time delay (trt) between TL and return-back 100 PPS signal (Trt).…”
Section: Localmentioning
confidence: 99%
“…For example, the relative frequency stability can reach 5×10 −15 @1 s and 2×10 −18 @1 day while using fiber to achieve remote 1 GHz frequency synchronization [7], and using fiber to transmit mode-locked laser pulses can even achieve fs-level time synchronization [8,9]. However, the existing technologies mainly focus on the transmission and synchronization of the reference time and frequency, only requiring the phase difference between frequency signals to remain stable [7], [10]- [12]. The phase difference is constant during each independent running state, but when the system experiences operations from shutdown to restart, or changing the length of fiber link, the phase difference value after entering the steady state again will change.…”
Section: Introductionmentioning
confidence: 99%
“…Many teams have proposed a variety of networking RF frequency dissemination scheme [10]- [15]. L. Q. Yu et al, for example, proposed and demonstrated a networking scheme for a tree topology of 1 GHz RF frequency signal, and discussed the network capacity based on wavelength division multiplexing technology [12].…”
Section: Introductionmentioning
confidence: 99%